Genetic Diversity of Prolactin Gene in Two Strains of Japanese Quail (Coturnix coturnix japonica) in Nigeria - Eichie , F.O.; Salako, A.E.; Aggrey, S.E. (International Journal of Poultry Science, 2016)
Background: Among poultry species, quail is the easiest to produce, yet no proper breeding strategy exist in Nigeria. However, data on production characteristics and genetic diversity among quail populations in Nigeria is scant. Objective: This study was carried out to investigate the genetic diversity, relationship and population structure in two Japanese quail strains (Albino and wild) using a restricted fragment length polymorphism marker in the prolactin (PRL) gene. Methodology: Fifteen quail from each strain were sampled in 5 geographical regions in Nigeria (Kano, Jos, Umudike, Port Harcourt and Ibadan). Polymerase chain reaction (PCR) and electrophoresis was used to characterize a 24 base pair (bp) insertion/deletion in a 358 bp PCR product. Results: The genetic variability using allele frequency, molecular variance, deviation from Hardy-Weinberg (H-W) equilibrium using the phylogenies package (PHYLIP) and analysis of molecular variance (AMOVA) were obtained. The frequency of insertion (A allele) was similar for both strains in the Ibadan, Jos and Umudike populations, however, the allele frequency was 0.73 and 0.50 for the Albino and Wild strains, respectively in Kano 0.57 and 0.70, respectively for the Albino and Wild strains in Port Harcourt. Whereas, there were no deviations from HWE for both strains, in Ibadan, Jos and Umudike, the populations in Kano and Port Harcourt deviated from H-W equilibrium. The AMOVA analysis showed 4.04% population difference, 1.17% variation among individuals and 94.25% within individuals. Conclusion: Prolactin is an important gene for reproduction and it’s segregation could be assessed for reproductive capacity. The delineation of genetic diversity in these populations allows for innovative selective breeding and conservation strategies to be developed.